Role of Actin Cytoskeleton Reorganization in Polarized Secretory Traffic at the Immunological Synapse - Calvo, Victor; Izquierdo, Manuel (Frontiers in Cell and Developmental Biology, 2021)
T cell receptor (TCR) and B cell receptor (BCR) stimulation by antigen presented on an antigen-presenting cell (APC) induces the formation of the immune synapse (IS), the convergence of secretory vesicles from T and B lymphocytes towards the centrosome, and the polarization of the centrosome to the immune synapse. Immune synapse formation is associated with an initial increase in cortical F-actin at the synapse, followed by a decrease in F-actin density at the central region of the immune synapse, which contains the secretory domain. These reversible, actin cytoskeleton reorganization processes occur during lytic granule degranulation in cytotoxic T lymphocytes (CTL) and cytokine-containing vesicle secretion in T-helper (Th) lymphocytes. Recent evidences obtained in T and B lymphocytes forming synapses show that F-actin reorganization also occurs at the centrosomal area. F-actin deletion at the centrosomal area appears to be involved in centrosome polarization. In this review we deal with the biological significance of both cortical and centrosomal area F-actin reorganization and some of the derived biological consequences.